Sistema reconfigurável pulse/receiver para excitação ultrassônica convencional e chirp codificada usando modulação de amplitude de pulso - Medeiros, Renan Antonio Corrêa (2022)
Several research groups have addressed the study of new ultrasonic excitation techniques to optimize the relationship between spatial resolution and penetration depth of the acoustic beam. However, the generation of complex waveforms with short pulses using conventional sinusoidal excitation (CCS) and long pulses from coded chirp excitation (CCE), as well as the analysis of the ultrasound echoes generated by both techniques, requires appropriate electronic instrumentation, which is not always available to researchers. This dissertation presents a reconfigurable, flexible, and fully programmable arbitrary waveform generator (AWG) pulser/receiver (P/R) system for ECS and ECC research activities. The pulse-echo system consists of a Matlab-based graphical user interface GUI to control and acquire raw ultrasound echoes from a hardware structure formed by a DE2-115 FPGA kit and a proprietary board with the reception modules. (RX) and transmission (TX). The prototype board includes the AWG MD2134, which uses the pulse amplitude modulation technique, and the RX module, formed by the MD0100 T/R switch, VCA810 variable gain amplifier, and the 12-bit 80 MSPS ADS6123 analog-to-digital converter. The FPGA was programmed with Quartus Prime Lite software and, in addition to the codes implemented in VHDL language and intellectual property blocks, it includes a 32-bit Nios II processor to control and transfer the data packet with a length of 16384 samples to a computer. The characterization and performance tests of the system were carried out with RC load, two single-element transducers with a central frequency of 1.6 MHz and 5 MHz, and an ultrasound phantom with a speed of sound of 1540 ± 6 m/s. ECS signals of 3 cycles with a central frequency of 1.6 MHz and 5 MHz, and ECC with a duration of 5 µs and 10 µs, and frequency bands of 1.6 MHz ± 1 MHz and 5 MHz ± 2 MHz were evaluated. After acquiring phantom signals, filtering, envelope detection, and logarithmic compression steps were performed to calculate the speed of sound and FWHM parameters of 13 targets with a diameter of 1 mm, spaced at 1 cm in the axial direction. The experimental results of the mean sound propagation speed for ECS and ECC were 1566.51 ± 28.40 m/s and 1585.24 ± 62.50 m/s, with a mean error of 1.78% and 3.62%, respectively. The ECS method also showed better FWHM values, resulting in 1.48 ± 0.44 mm, compared to ECC of 2.12 ± 0.27 mm. The results show that the proposed system is suitable for future medical and industrial instrumentation applications, in addition to the study of coded excitation techniques through the application of matched and mismatched filters in the reception to detect deeper targets with the same spatial resolution provided by conventionally excited systems.